2008
DOI: 10.1093/annonc/mdn058
|View full text |Cite
|
Sign up to set email alerts
|

Adding cetuximab to capecitabine plus oxaliplatin (XELOX) in first-line treatment of metastatic colorectal cancer: a randomized phase II trial of the Swiss Group for Clinical Cancer Research SAKK

Abstract: Differences in response rates between the treatment arms indicate that cetuximab may improve outcome with XELOX. The correct place of the cetuximab, oxaliplatin and fluoropyrimidine combinations in first-line treatment of MCC has to be assessed in phase III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 22 publications
(43 reference statements)
2
94
1
Order By: Relevance
“…Prelimary data from two small randomized phase II studies (Borner et al, 2006;Heinemann et al, 2006) were also presented. One study showed that addition of Cx to XELOX increased RR (from 27 to 43%) and another study showed that the combination of XELOX and Cx increased RR from 42 to 66% compared with XELIRI and Cx.…”
Section: First-line Therapymentioning
confidence: 99%
“…Prelimary data from two small randomized phase II studies (Borner et al, 2006;Heinemann et al, 2006) were also presented. One study showed that addition of Cx to XELOX increased RR (from 27 to 43%) and another study showed that the combination of XELOX and Cx increased RR from 42 to 66% compared with XELIRI and Cx.…”
Section: First-line Therapymentioning
confidence: 99%
“…All these studies indicated that only a subgroup of patients treated with cetuximab may benefit from the drug (Rosenberg et al, 2002;Van Laethem et al, 2003;Cunningham et al, 2004;Saltz et al, 2001Saltz et al, , 2004Tabernero et al, 2004;Jennis et al, 2005;Borner et al, 2006;Folprecht et al, 2006;Venook et al, 2006;Wilke et al, 2006). Based on preclinical findings, it should be outlined that the trials including cetuximab have been performed in patients who expressed EGFR protein in primary tumours based on immunohistochemistry (IHC).…”
mentioning
confidence: 99%
“…After the initial pivotal randomised phase II BOND study which demonstrated the ability of cetuximab to circumvent chemotherapy resistance , a series of randomised phase II -III trials for EGFR-targeted monoclonal antibodies (mAbs) have been reported. Table 2 shows the results of these trials Jonker et al, 2007;Tejpar et al, 2007;Van Cutsem et al, 2007Borner et al, 2008;Ciuleanu et al, 2008;Heinemann et al, 2008;Sobrero et al, 2008;Wilke et al, 2008;Bokemeyer et al, 2009;Hecht et al, 2009). All these studies supported the biological activity of cetuximab in advanced CRC.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 78%